Government failure: does government failure occur? - Ramesh, Sangaralingam (Henry Stewart Talks, 2019)
Government failure, Common Agricultural Policy (CAP), Market distortions, Public choice theory, Conflicting interests, Short-termism, Regulatory capture, Dumping, Externalities